Underworld - Wiseman, Len; Screen Gems; Lakeshore Entertainment (United States Sony Pictures Home Entertainment, 2003)
A vampire warrior becomes entangled in a centuries-long war between vampires and werewolves, discovering hidden secrets that could change the fate of both species forever.
Originally released as a motion picture in 2003.
Rated R.
Keywords: Vampires; Werewolves